Recombination Sites on Hybrid Chromosomes in S. pastorianus share Common Sequence Motifs and define a Complex Evolutionary Relationship between Group I and II Lager Yeasts - BOND, URSULA (My University, 2017)
Saccharomyces pastorianus, referred to as lager yeasts, are hybrids of S. cerevisiae and S. eubayanus. Isolates within the species are divided into two groups (I and II) based on chromosome structure and composition. Following the hybridisation, the parental chromosomes underwent homeologous recombination, generating a set of hybrid chromosomes unique to the species. Here, we assessed the recombination events in seven lager yeast genomes to more clearly define the evolutionary route of lager yeasts. Meta-analysis of the recombination epicentres, as well as a detailed analysis of recombination events at the MAT locus, reveals a more complex evolutionary relationship between the group I and II lager yeasts than previously considered and identifies several divergent routes of evolution leading to the current S. pastorianus strains. We show that recombination epicentres contain sequential runs of pyrimidines, often flanked by purines, on one strand of the DNA, and identify two common sequence motifs present in >80% of the recombination epicentres, indicating that a common mechanism might account for the recombination events. Taken together, the data support a sequential hybridisation model of evolution for the two types of lager yeasts and suggest that the genomes of this newly emerged species are highly dynamic and continually evolving.
Keywords: Saccharomyces pastorianus; Recombination epicentres; Lager yeasts; Common motifs; Evolution; Hybrid chromosomes; Genes & Society